Pengaruh Influencer Marketing dan E-WOM terhadap Keputusan Pembelian dengan Purchase Interest sebagai Variabel Intervening pada Parfum Brand Posh di Shopee - Muhammad Nanda Dwi Sudarmo; Hanif Ahmadi (ARZUSIN, 2026)
Competition in the local perfume industry in e-commerce requires the implementation of effective digital marketing strategies, particularly through influencer marketing and electronic word of mouth (E-WOM), to enhance consumer purchase decisions. This study aims to analyze the effect of influencer marketing and E-WOM on purchase decisions, with purchase intention as an intervening variable, for the Posh perfume brand on Shopee. This study employed a quantitative approach with an explanatory research method. Data were collected through questionnaires administered to 150 respondents in Semarang City selected using purposive sampling, and were then analyzed using Partial Least Squares (PLS). The results showed that influencer marketing and E-WOM had a positive and significant effect on both purchase intention and purchase decisions. In addition, purchase intention was also proven to have a positive effect on purchase decisions and to mediate the relationship of influencer marketing and E-WOM with purchase decisions. These findings contribute to strengthening the study of digital marketing and consumer behavior in the context of e-commerce, while also showing that influencer-based marketing strategies and E-WOM are effective in increasing purchase intention, which in turn affects purchase decisions. The implications of this study underscore the importance of optimizing collaboration with credible influencers and managing consumer reviews positively to strengthen trust and encourage purchases.